2022
DOI: 10.1177/09544089221074852
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of titanium alloys machinability used for medical applications

Abstract: CNC machining manufacturing is critical to the development of biomedical industries, especially orthopaedic implants. Understanding a material's machinability under different cutting conditions is essential for component design as well as for optimizing the machining process. Despite their widespread use in the biomedical industry, α + β-type titanium (Ti) alloys, such as Ti-6Al-4V and Ti-6Al-7Nb, are being replaced by β or near β-type Ti alloys like Ti-13Nb-13Zr Ti alloy due to issues associated with Vanadium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…While the previous work, 9 suggested a better surface finish in Ti6Al7Nb micro-milled surfaces, reports for turning 10,11 showed the opposite trend. Nevertheless, Mello et al 11 found that the turning conditions required to achieve the same (and optimal) surface roughness in both alloys were identical, indicating that they exhibit similar machinability.…”
Section: Introductionmentioning
confidence: 68%
“…While the previous work, 9 suggested a better surface finish in Ti6Al7Nb micro-milled surfaces, reports for turning 10,11 showed the opposite trend. Nevertheless, Mello et al 11 found that the turning conditions required to achieve the same (and optimal) surface roughness in both alloys were identical, indicating that they exhibit similar machinability.…”
Section: Introductionmentioning
confidence: 68%